GIS Application Analysis Earthquake Data to Evaluate Risk Assessments of Seismic Hazard in Kurdistan of Iraq Using Probabilities - Mohammed, Rebaz Nawzad; Mohammed, Nabaz Ghareeb; Faraj1, Kamaran H. M. Ali (Sulaimani Journal for Pure and Applied Sciences, 2015)
Earthquakes in Kurdistan of Iraq are unorganized natural disaster, that happens without any schedule or any knowledge of when and where they may occur. However, it is important to know where and when they may happen or at least identify the risk locations, strength of the danger, numbers of occurrence per area (density) and predict the future earthquakes if possible, which are the key issues of this paper. The answer to these issues can be achieved through earthquake data evaluation. Hence it is important to look into the earthquake data from the past, and evaluates them through the power of GIS (Geographical Information System) application; this will build a method that will develop the access to the answers to the key issues through a spatial analytical procedure, as the answer helps future planning and risk assessments. GIS can evaluate seismic hazard and risk analysis, as it demonstrates an environment with many features that uses to carryout statistical and spatial analysis efficiently. The application first looks at the data in details, afterwards it allocates the information to each administrative area in the province of Kurdistan accordingly and maps the data vividly to produce graphical results to the issues and their answers, that are easier to illustrate the results. Eventually, the data needs to be examined for any available patterns that help for the future earthquake prediction, if there are any data. problem and your proposed technique to address it.
Keywords: GIS; earthquakes; seismic hazard; risk Assessments; Kurdistan of Iraq